2003
DOI: 10.1097/01.inf.0000095197.72976.4f
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin, C-reactive protein and leukocyte count in children with lower respiratory tract infection

Abstract: High PCT and CRP values show a significant correlation with the bacterial etiology of lower respiratory tract infection. PCT and CRP show good sensitivity for distinguishing pneumococcal from other etiologies. PCT shows higher specificity than CRP. PCT and CRP can help make decisions about antibiotic therapy in children with lower respiratory tract infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 27 publications
(38 reference statements)
2
61
0
2
Order By: Relevance
“…The serum level of PCT was measured by using an enzyme-linked fluorescence assay (VIDAS � BRAHMS PCT assay; Biomerieux, Lyon, France), according to the manufacturer' s instructions; the detection limit of this assay is 0.05 ng/mL. The upper limit of reference interval used in this study was 0.5 ng/mL, as suggested by the manufacturer, whereas the upper limits for elevated serum PCT level were 1.0 ng/mL, which has been suggested by Moulin et al [8], and 2.0 ng/mL, which has been suggested by Toikka et al [9] and Prat et al [15].…”
Section: Measurement Of Pct Level Crp Level Esr and Wbc Countmentioning
confidence: 74%
“…The serum level of PCT was measured by using an enzyme-linked fluorescence assay (VIDAS � BRAHMS PCT assay; Biomerieux, Lyon, France), according to the manufacturer' s instructions; the detection limit of this assay is 0.05 ng/mL. The upper limit of reference interval used in this study was 0.5 ng/mL, as suggested by the manufacturer, whereas the upper limits for elevated serum PCT level were 1.0 ng/mL, which has been suggested by Moulin et al [8], and 2.0 ng/mL, which has been suggested by Toikka et al [9] and Prat et al [15].…”
Section: Measurement Of Pct Level Crp Level Esr and Wbc Countmentioning
confidence: 74%
“…Others have found sensitivity and specificity values for procalcitonin in similar ranges (Table 3) [2,5,11,14,21,26,29,30,33]. However, the results reported by Worthington et al were quite different: serum procalcitonin did not help distinguish between infectious and noninfectious causes of prosthetic hip loosening [41].…”
Section: Discussionmentioning
confidence: 91%
“…We specified the following exclusion criteria: patients with inflammation other than an orthopaedic infection (eg, autoimmunity, intercurrent febrile infection) (to avoid interference with other inflammatory processes); patients with other possible preconditions for elevated inflammatory markers, such as chronic inflammatory diseases, obesity (BMI [ 30), viral infections, malignancies, or heavy smoking; and patients with renal, hepatic failure, or deficiencies of the immune system. Patients were recruited between March 2008 and June 2010 in the Department for Orthopaedic Surgery, Medical University of Graz (Graz, Austria).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] The highest value is seen in association with gram-negative sepsis and bacterial meningitis; levels increase moderately when local bacterial infections such as pyelonephritis and pneumonia are present. [10][11][12] Some studies showed that a high PCT level in patients with Plasmodium falciparum malaria correlate with severity and poor prognosis of the disease. 13 To our knowledge, PCT serum levels have not been evaluated in VL patients.…”
mentioning
confidence: 99%